Effect of film types on thermal response, cellular structure, forming defects and mechanical properties of combined in-mold decoration and microcellular injection molding parts. (30th November 2021) - Guo, Wei; Yu, Zhihui; Wei, Wenting; Meng, Zhenghua; Mao, Huajie; Hua, Lin
Highlights: The thermal response at the melt filling stage of IMD/MIM process with different types of polymer films was revealed through numerical simulation. The cellular structure of IMD/MIM parts molded with different films was analyzed by the SEM image. The effect of film types on forming defects of the IMD/MIM parts was investigated by the combination of simulation and experiment. The influence of different films on the mechanical properties of the IMD/MIM was studied by the physical experiment. Abstract: Different types of polymer films were used in the combined in-mold decoration and microcellular injection molding (IMD/MIM) process. The multiphase fluid-solid coupled heat transfer model was established to study the thermal response at the melt filling stage in the IMD/MIM process. It was found that the temperature distributed asymmetrically along the thickness direction due to the changed heat transfer coefficient of the melt on the film side. When polyethylene terephthalate (PET) films were applied, the temperature of the melt-film interface increased faster and to be higher at the end of melt filling stage in comparison with the application of polycarbonate (PC) and thermoplastic polyurethane (TPU) films. And the effects of film types on the cellular structure, forming defects and mechanical properties of IMD/MIM parts were also studied experimentally. The results showed that the film types had no obvious effect on the cells size in the transition layer and the mechanical properties of the parts. Under certain film thickness, the offset distance of core layer was the largest with PET film used, while the offset distance was the smallest with TPU film used. And similar results were found for the warpage of the parts. However, an exactly opposite change occurred for the thickness of film-side transition layer and the bubble marks on the surface of the parts. Graphical abstract: Image, graphical abstract